Relevansi Teknologi Pendidikan dan Mutu Pendidikan - Zaedun Na'im (STAI Ma'had Aly Al-Hikam Malang, 2019)
The quality of education is an important issue in the world of education, because by looking at the quality of education can be a reflection of the success of education that is carried out. If the quality of education is good, it can be said that in the implementation of good education, likewise if the quality of education is low, then it can be assumed that in the implementation of education there are serious problems. Therefore this paper was appointed to inspire education observers to pay more attention in maintaining and overseeing the quality of education so that the output or graduates can be relied upon. This article review method uses qualitative. While presenting data using descriptive analysis and designed using a central approach by looking for literature that discusses the quality of education and education technology. The results of this study are the relevance or relationship between educational technology and the quality of education, because the quality of education with regard to everything that achieves the achievement of quality education both in terms of student achievement, teaching quality, and school performance can be achieved well through an educational technology approach. That is because with educational technology involving people who have an important role in the educational problem, it is then regulated by standardized procedures and the next stage is organized for analysis and finding solutions to solve them